Strategi Pertumbuhan Bisnis di Bidang Pendidikan : Analisis Konsep Pertumbuhan, Siklus Pengembangan, dan Pendekatan Growing the Core dalam Perspektif Pemasaran Pendidikan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
Educational businesses face unique challenges because they are not solely oriented toward financial profit, but also toward social values, institutional sustainability, and the improvement of human resource quality. Educational institutions are required to balance educational idealism with professionalism and competitiveness. This study aims to explain growth strategies in the education business sector through a conceptual approach and literature analysis. The main focus of the study includes the concept of growth, the growth cycle of educational businesses, growth strategies, the growing the core approach, and educational marketing strategies. The research method used is descriptive qualitative with a literature review approach. Data were obtained from various literature sources, such as academic journals, educational books, and publications related to educational management. The findings indicate that sustainable growth in educational businesses largely depends on an institution’s ability to strengthen its core values, innovate learning services, improve management quality, expand markets ethically, and build public trust through educational, transparent, and quality-oriented marketing strategies.